Building Staff Capacity through Reflecting on Collaborative Development of Embedded Academic Literacies Curricula - Thies, Linda (Journal of University Teaching and Learning Practice, 2016)
Most Australian universities articulate some policies around the integration of graduate learning outcomes in courses. This paper draws on a Federal Government funded project that adopted a developmental approach to students’ acquisition of course learning outcomes, through the embedding of academic literacies in course curricula. The project was part of a Higher Education Participation and Partnership Program (HEPPP), which focused on courses with a high proportion of students from a low socio-economic status (SES) background. However, the project took an inclusive approach to curriculum development by focusing on the needs of all students. In describing this project, the paper aims to explore the challenges and advantages of collaborative curriculum development. The findings, which are based on individual interviews with the project partners suggest that increased collaboration between course team members and professional staff, and the opportunity to reflect built the capacity of all staff, specifically their understanding of academic literacies. Evaluation of the project helped to confirm that a curriculum renewal process needs to ensure that members of course teams have time to fully engage in collaborative reflection. The evaluation supported a move to a more cooperative approach to curriculum development.